Supply Chain Management in Hospitals - Impetus from Organizational and Behavioral Theories - Hinterplattner, Melanie; Gerschberger, Markus; Staberhofer, Franz (Journal of Marketing Development and Competitiveness, 2016)
The purpose of this paper was to discuss a theoretical foundation for supply chain management (SCM) in hospitals based on organizational and behavioral theories with the aim of explaining how hospitals can structure and manage their supply chain (SC). The discussed theories help to better understand SCM in hospitals. The market-based view enables the analysis of the competitive environment. The resource-based view helps to develop an understanding of what the key resources are. Network and stakeholder theory give guidance on how to identify most relevant partners. As relationships between different actors exist by nature, principal-agent theory helps to reduce agency-costs.